Élaboration et caractérisation de l’effet du dopage des couches minces de SnO2 déposées par spray pyrolyse pour l’application optoélectronique - KHALFALLAH, Mehdi; ENCA/GUERMAT Noubeil (UNIVERSITE DE M’SILA, 2023)
This thesis covers the elaboration and characterization of undoped and doped tin oxide (SnO2) films as a function of the doping elements (Ni, Zn and F) by the pyrolysis spray method. The study and determination of optoelectronic quantities (transmittance, optical gap, electrical resistivity, etc.) before and after doping with these elements is the subject of chapter III of this thesis. For this, several techniques were used in this work for the characterization of our films: X-ray diffraction (XRD) for the structural study, Scanning electron microscopy (SEM) for the morphological properties, the contact angle for the surface properties, the UV-visible spectrophotometer for the optical properties and the method of the four points/or the Hall effect for the electrical properties. The summary of the properties of the doped films gave: The UV-Vis results showed an improvement in transparency and a widening of the optical gap for the doped SnO2 films compared to the undoped film, with a large value of 85% and Eg = 3.88 eV for the doped. 5.6 at.% Ni film. This is an important optical characteristic for use as a transparent electrode in thin film solar cells. The electrical results showed a very low electrical resistivity, in the order of 2.245×10-4 Ω.cm, it was obtained for the 20.7 at.%F doping, and with an acceptable resistivity equal to 4.400×10-2 Ω.cm for the SnO2 : 5.6 at.%Zn doped film , but less effective for the objective targeted in this study. After these results it can be concluded that the optimum conditions are obtained for the films SnO2:5.6 at.%Ni or SnO2:20.7 at.%F, which can be used to fabricate thin films as conductive transparent electrodes in the thin film solar cells. In this work we also contributed to the simulation of the transmittance using the Matlab software. A Matlab program has been designed based on the FDFD method to simulate the optical response of a semiconductor layer. A simplification of the structural state of the layer was necessary to allow the discretization of Maxwell's equations in the structure with the necessary boundary conditions. The approach is initial and optimization work remains our perspective.
Keywords: Thin films, SnO2/Ni, SnO2/Zn, SnO2/F, Pyrolysis spray, XRD, SEM, Contact angle, Transmittance, Solar cell